Aturan Wajib Bagi Konsumen Menjadi Anggota Happy Kiddy Ditinjau Dari Hukum Perlindungan Konsumen - Faliya Hakim; Theresia Louize Pesulima; Agustina Balik (TATOHI: Jurnal Ilmu Hukum, 2023)
Introduction: Consumer protection is an integral part of healthy business activities.Purposes of the Research: The purpose of this study is to understand and find out the obligations for consumers, who are members of Happy Kiddy, legal protection that can be given to consumers directly and to find out the extent of the binding power of the standard clauses on consumers, who become consumers in places that apply standard clauses. Methods of the Research: The method used in analyzing and reviewing is normative juridical.Results of the Research: The results of this study indicate that the inclusion of a standard clause made by Happy Kiddy, there is a clause that is contrary to Law Number 8 of 1999 concerning Consumer Protection. The negative impact for consumers with the inclusion of standard clauses from Happy Kiddy is the obligation of consumers to become Happy Kiddy members, consumers are vulnerable to becoming victims of business actors due to their weak position. The form of legal protection for consumers related to the inclusion of standard clauses carried out by Happy Kiddy business actors is contained in Article 18 paragraph (3) of the UUPK. In addition, the form of consumer protection related to the inclusion of standard clauses through supervision is carried out by BPSK and the District Court.